Analisis Terhadap Pemikiran Hasan Al-Banna, Sayyid Qutb, dan Ali Syariati Dalam Konteks Islam Kontemporer - Madani, Muhammad Rizki (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study discusses the views of contemporary scholars on Islamic political ethics, focusing on the thoughts of Hasan Al-Banna, Sayyid Qutb, and Ali Shariati. The background of the problem includes the challenges faced in implementing the principles of political ethics in the context of modern society. The method used is a qualitative literature study to analyze the works and thoughts of the three figures. The purpose of this study is to identify and understand the contribution of their thoughts to strengthening Islamic political ethics. The results of this study indicate that the thoughts of Hasan Al-Banna, Sayyid Qutb, and Ali Shariati emphasize the importance of Islamic values as the basis for fair and transparent political ethics. All three, despite their different approaches, agree that Islamic law must be the main guide in creating a just social and political order.